Comparison of Sublingual and Oral Doses of Misoprostol Before Intracavitary Brachytherapy For Cervical Cancer. - Lakdee, Chawalit; Sanbunlerng, Jariyaporn; Khongsukkho, Kesaraporn; Phosrithong, Siriporn; Kraisornkhaisri, Thanyaporn (Journal of Thai Association of Radiation Oncology, 2022)
Background: For locally advance cervical cancer radiotherapeutic treatment, external beam radiation (EBRT) and brachytherapy are treatment that target tumor sites with increased dose while reducing the dose to neighboring organs at risk. Cervical dilatation is recommended for Gynecologic procedure that involve intrauterine insertion with hysteroscopy and brachytherapy by several evidence-based guidelines . Misoprostol, an effective medication with various doses, routes and time intervals, is under investigation as a uterine cervical dilating agent. Objective: To evaluate the efficacy of oral misoprostol and sublingual for cervical dilatation in facilitation of tandem application to the cervix before the first intracavitary brachytherapy in patients with cervical cancer. Materials and methods: In this prospective, randomized, double-blind study, 91 patients had received either 400 µg of misoprostol 3 hours or 400 µg sublingually 30 minutes before the first intracavitary brachytherapy. All patients had received whole pelvic radiotherapy by 2-D or 3D-CRT with a total dose of 45-46 Gy plus image-guided High-Dose-Rate intracavitary brachytherapy 7 Gy × 4 fractions. Results: Median cervical widths in the oral and sublingual misoprostol groups before the first intracavitary brachytherapy were 6 mm and 7 mm, respectively, which were statistically significant different(P=0.049). Median pain scores for the oral and sublingual were similar (4 vs 4; P=0.452). Uterine cramping and shivering were more frequently presented in the sublingual than oral misoprostol group (36.9% vs 17.8%; P= 0.040 and 17.4% vs 2.2 %; P = 0.030). Other side effects such as nausea, vomiting diarrhea and fever did not differ between groups. There was no significant difference of dosimetric parameters in treatment planning brachytherapy planning between groups. Conclusions: Sublingual route of misoprostol was significantly more effective for cervical dilatation, but had more uterine cramping and shivering greater than oral route when administered for the first intracavitary brachytherapy in cervical cancer patients.